2020
DOI: 10.1007/s11356-020-10066-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Citrus limonia oil against cisplatin-induced nephrotoxicity

Abstract: Cisplatin is broadly used in the treatment of malignancies. However, the high incidence of nephrotoxicity following cisplatin use deters its clinical utility. Former studies have shown that the essential oils, obtained from Citrus limonia demonstrated significant anti-inflammatory and antioxidant effects. The aim of the current work was to evaluate the protective effects of Citrus limonia oil against cisplatin-induced nephrotoxicity. Thirty-two adult male mice were divided into four groups, eight mice each. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…However, CIS administration has been accompanied by nephrotoxicity, cardiotoxicity, hepatotoxicity, and ovarian toxicity. [13][14][15][16][17][18] Previous research suggests that CIS induces cytotoxicity in healthy tissue via continuous generation of reactive oxygen species (ROS), suppressing endogenous antioxidant enzymes, releasing free radicals, and inducing mitochondrial oxidative stress. [19,20] The continued generation of free radicals in the cells is responsible for inducing the pathogenic phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, CIS administration has been accompanied by nephrotoxicity, cardiotoxicity, hepatotoxicity, and ovarian toxicity. [13][14][15][16][17][18] Previous research suggests that CIS induces cytotoxicity in healthy tissue via continuous generation of reactive oxygen species (ROS), suppressing endogenous antioxidant enzymes, releasing free radicals, and inducing mitochondrial oxidative stress. [19,20] The continued generation of free radicals in the cells is responsible for inducing the pathogenic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Different hypotheses have been investigated and several studies performed to elucidate the etiology of CDDP nephrotoxicity [4] . It has been reported that CDDP can cause glutathione depletion, reactive oxygen species (ROS) production and an increase of inflammatory mediators and apoptotic markers resulting in cell injury and death [5] , [6] . However, this serious problem continues, and many patients are unable to continue treatment with CDDP for a sufficient period of time.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the mixture of LEO and a ginger extract substantially decreased the lipid peroxidation intensity in the liver and the brains of mice and increased the resistance of liver and brain lipids to oxidation and the activity of antioxidant enzymes in the liver ( 17 ). Abdel-Daim et al ( 18 ) found that treatment with limonia oil at 100 and 200 mg/kg BW improved all the biochemical alterations in a dose-dependent manner, which could increase the concentration of SOD, and decrease the concentration of MDA. CampêLo et al ( 19 ) found that LEO reduced the level of lipid peroxidation and increased the level of GSH and SOD, catalase and glutathione peroxidase in mouse hippocampus.…”
Section: Discussionmentioning
confidence: 99%